Gakman A. Technology of recreational and health activities in the summer camp outwork - Андрєєва, О. В.; Гакман, А. В. (Slobozhanskyi Herald of Science and Sport, 2011)
A technology of organization of recreational and health activities in the summer camp is theoretically justified and presented in the paper, which takes into account social and educational characteristics of a temporary children community. The stages of technology are presented and analyzed, the content of recreational health programs is represented according to the period of the child stay in summer camp.